Well-ordered ZnO nanowires with controllable inclination on semipolar ZnO surfaces by chemical bath deposition. (25th September 2018) - Cossuet, Thomas; Roussel, Hervé; Chauveau, Jean-Michel; Chaix-Pluchery, Odette; Thomassin, Jean-Luc; Appert, Estelle; Consonni, Vincent
Abstract: Controlling the formation of ZnO nanowire (NW) arrays on a wide variety of substrates is crucial for their efficient integration into nanoscale devices. While their nucleation and growth by chemical bath deposition (CBD) have intensively been investigated on non-polar and polar c -plane ZnO surfaces, their formation on alternatively oriented ZnO surfaces has not been addressed yet. In this work, the standard CBD technique of ZnO is investigated on ( 10 1 ̄ 2 ) and ( 20 2 ̄ 1 ) semipolar ZnO single crystal surfaces. A uniform nanostructured layer consisting of tilted ZnO NWs is formed on the ( 10 1 ̄ 2 ) surface while elongated nanostructures are coalesced into a two-dimensional compact layer on the ( 20 2 ̄ 1 ) surface. By further combining the CBD with selective area growth (SAG) using electron beam-assisted lithography, highly tilted well-ordered ZnO NWs with high structural uniformity are grown on the ( 20 2 ̄ 1 ) patterned surface. The structural analysis reveals that ZnO NWs are homoepitaxially grown along the polar c -axis. The occurrence of quasi-transverse and -longitudinal optical phonon modes in Raman spectra is detected and their origin and position are explained in the framework of the Loudon's model. These results highlight the possibility to form ZnO NWs on original semipolar ZnO surfaces. It also opens the way for comprehensively understanding the nucleation and growth of ZnO NW arrays on poorly and highly textured polycrystalline ZnO seed layers composed of nanoparticles with a wide range of non-polar, semipolar, and polar plane orientations. Eventually, the possibility to tune both the inclination and dimensions of well-ordered ZnO NW arrays by using SAG on semipolar surfaces is noteworthy for photonic and optoelectronic nanoscale devices.